Protective role of dexmedetomidine in unmethylated CpG-induced inflammation responses in BV2 microglia cells - Chen, Chen; Qian, Yanning (Folia Neuropathologica, 2016)
Unmethylated CpG DNA, as a stimulatory molecule, has potent pro-inflammatory effects in the central nervous system (CNS). Dexmedetomidine (DEX) has been confirmed to exert anti-inflammatory effects in CNS. Our study was aimed to explore the effects of DEX on tumor necrosis factor-α (TNF-α) expression in unmethylated CpG DNA-challenged microglia. In vivo, after 3 d intracisternal injection of ODN1668, we evaluated the severity of meningitis with or without DEX via pathobiology method and detected the expression of TNF-α from molecular and protein levels. In vitro, we explored whether the ODN1668 could activate microglia to express TNF-α and the inhibition mechanism of DEX. Our results demonstrated that DEX could alleviate the severity of ODN1668-induced meningitis. And while BV2 microglia was stimulated by ODN1668 for different time, TNF-α was increased in mRNA and protein levels but the effect was attenuated by DEX via decreasing phosphorylated AKT and ERK